Phytophthora Taxon Pgchlamydo is a Cause of Shoot Blight and Root and Collar Rot of Viburnum tinus in Italy - Ginetti, B (Plant disease, 2014)
The quarantine pathogen Phytophthora ramorum has recently been found on dying Viburnum tinus in the nursery area of Pistoia, central Italy (43°56'0″ N, 11°1'0″ E) (3). As part of a surveillance program aimed at detecting P. ramorum in this area, the Phytophthora taxon Pgchlamydo was consistently found associated with symptomatic V. tinus. The crowns of these plants were wilted, and some plants also showed root and collar rot and underbark necrosis. Water courses adjacent to the nursery with the infected V. tinus were tested for the pathogen. Samples from seven symptomatic plants were placed on a selective V8A-PARPNH medium within 24 h from sampling. Tissue pieces (2 mm2) of 12 baits (apple fruits) exposed for a week in water bodies were plated on the same medium. Cottony colonies arose after 2 to 3 days of incubation at 23°C in the dark and were transferred to potato dextrose agar (PDA) in purity. Mycelial DNA was extracted with a commercial kit (Sigma-Aldrich). The rDNA ITS region and a portion of the mtDNA cox1 gene were PCR-amplified and the amplicons digested with the restriction enzymes MspI and AluI (for the ITS region) and RsaI (for the cox1 gene region). Isolates R7 from V. tinus, and ES2M5, ES2M11, and ES1M12 from the water bodies belonged to the same taxon based on restriction analysis of both DNA regions coupled with ITS-rDNA sequence homology (GenBank Accession Nos. KJ396773 to 76). A BLAST search in GenBank found that all isolates had a 99% identity in the ITS-rDNA with the Phytophthora ITS Clade 6 member P. taxon Pgchlamydo. Sporangia produced after incubation in filtered pond water for 24 h were mostly ovoid (sometimes obpyriform), non-papillate, non-caducous. Some sporangia were emptied with external proliferation and had hyphal swellings. Thirty sporangia were measured and averaged 42.4 ± 6.2 × 29.9 ± 3.5 μm (range 30.0 to 56.1 × 22.5 to 38.0), with a length/width ratio of 1.4 ± 0.2 (1.2 to 2.0), and exit pores of 11.7 ± 1.5 μm (9.0 to 14.6). Optimum colony growth on V8A at 30°C was 4.4 ± 0.4 mm day-1, and the maximum temperature for growth was 32°C. Inoculation on twigs of Fagus sylvatica and V. tinus produced necrotic lesions of 2.6 ± 0.5 cm (2.1 to 3.5) and 4.7± 0.5 cm (3.8 to 5.6) respectively after 3 weeks of incubation at 23°C in the dark. Inoculation on V. tinus leaves resulted in lesions averaging 3.3 ± 1.1 × 2.1 ± 0.6 cm (range 2 to 5 × 1.5 to 3) after 2 weeks of incubation at 23°C in the dark. Control plant material showed no symptoms.The Phytophthora taxon Pgchlamydo has been reported on several ornamental and woody species, including Arctostaphylos sp., Camellia spp., Laurus nobilis, Buxus sempervirens, Rhododendron sp., Arbutus unedo, Prunus sp., Pseudotsuga sp., and Sequoia sempervirens, in North America and Europe (1,2). This is the first report, to our knowledge, of this taxon on V. tinus in Italy. V. tinus is widely sold in European nurseries, and it is also one of the most common hosts of P. ramorum (4). The fact that V. tinus is a host for both oomycetes, and the two microorganisms induce a similar symptomology (wilt), might complicate the control efforts of the phytosanitary inspection services aimed at restricting P. ramorum foci in Europe. References: (1) C. L. Blomquist et al. Plant. Dis. 96:1691, 2012. (2) C. M. Brasier et al. Mycol. Res. 107:277, 2003. (3) B. Ginetti et al. Plant. Dis. 98:423, 2104. (4) S. Prospero et al. Plant Pathol. 62:1063, 2013